The substantive independence of the judiciary under the constitutions of Bangladesh and Malaysia : A comparative study / M. Ehteshamul Bari - M. Ehteshamul, Bari (2011)
The present research work, a comparative study as to the existing systems of appointment of judges in Malaysia and Bangladesh which is undertaken to examine its strengths and understrengths and to recommend a suitable mode for appointing judges of the superior courts for excluding patronage appointment and ensuring the appointment of men 'of stem stuff and tough fibre, unbending before power' in the higher judiciary, is divided into five chapters.